CK20 and CK5/6 Immunohistochemical Staining of Urothelial Neoplasms: A Perspective - Mohammed Akhtar; Sameera Rashid; Mohamed Ben Gashir; Noheir Mostafa Taha; Issam Al Bozom (Advances in Urology)
Cytokeratins belong to the family of intermediate filaments. They are expressed in a highly specific manner in epithelial cells where they play a crucial role in the integrity and mechanical stability of the cells. Several types of cytokeratins have been described in normal as well as neoplastic urothelium. In the case of urothelial neoplasms expression of CK20 and CK5/6 has been shown in several studies to have diagnostic and prognostic implications. Thus, low-grade urothelial carcinoma manifests CK expression limited to the umbrella cells, while high-grade tumors usually have an expression in the entire thickness of the urothelium except for the basal layer. CK5/6 expression on the other hand is expressed in the basal cells in all low-grade and some high-grade urothelial carcinomas. Diffuse CK20 staining accompanied by loss of CK5/6-positive basal layer is usually associated with aggressive clinical behavior. Double staining of the slides for these cytokeratins may facilitate proper interpretation and correlation.